Insights into shell deposition in the Antarctic bivalve Laternula elliptica: gene discovery in the mantle transcriptome using 454 pyrosequencing - Clark, Melody S; Thorne, Michael AS; Vieira, Florbela A; Cardoso, João CR; Power, Deborah M; Peck, Lloyd S (BMC genomics, 2010)
Background The Antarctic clam, Laternula elliptica , is an infaunal stenothermal bivalve mollusc with a circumpolar distribution. It plays a significant role in bentho-pelagic coupling and hence has been proposed as a sentinel species for climate change monitoring. Previous studies have shown that this mollusc displays a high level of plasticity with regard to shell deposition and damage repair against a background of genetic homogeneity. The Southern Ocean has amongst the lowest present-day CaCO 3 saturation rate of any ocean region, and is predicted to be among the first to become undersaturated under current ocean acidification scenarios. Hence, this species presents as an ideal candidate for studies into the processes of calcium regulation and shell deposition in our changing ocean environments. Results 454 sequencing of L. elliptica mantle tissue generated 18,290 contigs with an average size of 535 bp (ranging between 142 bp-5.591 kb). BLAST sequence similarity searching assigned putative function to 17% of the data set, with a significant proportion of these transcripts being involved in binding and potentially of a secretory nature, as defined by GO molecular function and biological process classifications. These results indicated that the mantle is a transcriptionally active tissue which is actively proliferating. All transcripts were screened against an in-house database of genes shown to be involved in extracellular matrix formation and calcium homeostasis in metazoans. Putative identifications were made for a number of classical shell deposition genes, such as tyrosinase, carbonic anhydrase and metalloprotease 1, along with novel members of the family 2 G-Protein Coupled Receptors (GPCRs). A membrane transport protein (SEC61) was also characterised and this demonstrated the utility of the clam sequence data as a resource for examining cold adapted amino acid substitutions. The sequence data contained 46,235 microsatellites and 13,084 Single Nucleotide Polymorphisms(SNPs/INDELS), providing a resource for population and also gene function studies. Conclusions This is the first 454 data from an Antarctic marine invertebrate. Sequencing of mantle tissue from this non-model species has considerably increased resources for the investigation of the processes of shell deposition and repair in molluscs in a changing environment. A number of promising candidate genes were identified for functional analyses, which will be the subject of further investigation in this species and also used in model-hopping experiments in more tractable and economically important model aquaculture species, such as Crassostrea gigas and Mytilus edulis .